EKONOMI ISLAM SALAH SATU MODEL ALTERNATIF STRATEGI MEREKATKOKOHKAN NKRI - Arwani, Agus (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
The situation these days we see no effort certain groups that seek to divide NKRI both from within and foreign countries. Currently, Indonesia has lost its way and the grip of ideology in the life of nation and state. The reappearance of the Islamic economic system, both in the world and Indonesia as we have seen since about three or four decades has led to a variety of views and attitudes. It is undeniable, that the designation of Islamic economics spawned a diverse impression. For some people, the word âIslamâ Islamic Economics positioned on a very exclusive place, thus eliminating keftrahannya as order value for all mankind (rahmatan lilâalamin). The concept of well-being (rahmatan lilâalamin) contained in Islamic economics aims to realize a just and prosperous society baldatun thoyyibatun wa robbun ghofur can be a safe and prosperous country and can realize resistance NKRI.Keyword: Islamic Economics, Model, Alternative, Strategy, NKRI